ACADEMIC AND VOCATIONAL QUALIFICATIONS FOR SECONDARY VOCATIONAL EDUCATION GRADUATES - Svetlana А. Efimova (Russian State Vocational Pedagogical University, 2016)
The aim of the study is to provide scientific and methodological basis for competency-based assessment including differentiation between academic and vocational qualifications used for educational programs in teaching applied qualifications. Methods. The methods involve systematic activity and competency-based approaches, structural-functional analysis, analysis, generalization, benchmarking. Results. The issue of differentiation between qualifications, acquired by vocational education organizations graduates is carried out. The analysis is carried out according to two directions - academic and practice-oriented. It has become evident that the mentioned educational results have quite different customers.The role of the state as a customer of academic qualifications and a mediator between the labor market (its needs are expressed in professional standards) and vocational education system is justified. An assessment sample is described. The sample includes two patterns of assessing the quality of education: vocational practice-oriented and academic assessment. Scientific novelty. Тhe sample of competency-based assessment in the system of vocational education is proved. The sample is designed to identify academic and vocational qualifications acquired by vocational education organizations graduates. The article specifies the definitions referring to the problem of qualifications assessment in the conditions of forming National qualifications system in the Russian Federation. Practical significance. The results of the research may be of some interest to researchers of applied qualifications, educators, specialists of educational authorities and vocational education institutions and can be used in modernization processes of regional assessment systems in vocational education.